1984
DOI: 10.1021/ac00271a028
|View full text |Cite
|
Sign up to set email alerts
|

Determination of milligram amounts of sulfur in hydrocarbons by constant current coulometry

Abstract: A new method for transforming trace amounts of elemental sulfur dissolved in hydrocarbons quantltatively to thiosulfate is developed. The sensltlvlty and accuracy of the method were checked by titratlng 1 m L samples of sodlum thlosulfate containlng sulfur in the range of 3.22 X to 6.85 X lo-'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…In Table 3, the sulfur concentrations of all the gasoline samples tested are presented. The obtained percentage by weight of total sulfur level in all the gasoline samples analyzed were observed to fall below the range of the reported sulfur level of 0.05-0.30 wt% in Nigerian refined petroleum products as established by past studies (Farroha et al, 1984;Adegbite, 1989;Oderinde, 1989;Tijjani et al, 2012) and the sulfur level limit of 0.1 wt% for gasoline recommended by the Department of Petroleum Resources Nigeria (2010). However, it was also observed that sulfur level in 89.9% of gasoline samples exceeded the 0.003-0.008 wt% (30-80 ppm) limit specified by the U.S. Environmental Protection Agency (2013).…”
Section: Methodscontrasting
confidence: 59%
See 1 more Smart Citation
“…In Table 3, the sulfur concentrations of all the gasoline samples tested are presented. The obtained percentage by weight of total sulfur level in all the gasoline samples analyzed were observed to fall below the range of the reported sulfur level of 0.05-0.30 wt% in Nigerian refined petroleum products as established by past studies (Farroha et al, 1984;Adegbite, 1989;Oderinde, 1989;Tijjani et al, 2012) and the sulfur level limit of 0.1 wt% for gasoline recommended by the Department of Petroleum Resources Nigeria (2010). However, it was also observed that sulfur level in 89.9% of gasoline samples exceeded the 0.003-0.008 wt% (30-80 ppm) limit specified by the U.S. Environmental Protection Agency (2013).…”
Section: Methodscontrasting
confidence: 59%
“…petroleum products as established by earlier studies (Farroha et al, 1984;Adegbite, 1989;Oderinde, 1989;Tijjani et al, 2012) and the sulfur level limit of 0.3wt% in diesel recommended by DPR. It was also observed that sulfur levels in 94.44% of diesel samples were above 0.05 wt% (500 ppm) limit specified by the U.S. Environmental Protection Agency.…”
mentioning
confidence: 93%
“…The accuracy of the use of UV-Vis for sulphur determination is in consonance with what was reported by Adetunji et al [30]. The percentage by weight of sulphur in the fuel samples were found to be in consonance with those reported in previous studies within the range of 0.05-0.30 wt.% in Nigerian refined petroleum products [36,39]. It was also observed that sulphur levels in the diesel samples were below the 0.05 wt.% (500 ppm) limit specified by the United States Environmental Protection Agency (USEPA).…”
Section: Concentrations Of Sulphur In the Fuel Productssupporting
confidence: 89%
“…Reaction of elemental sulfur and polysulfides with sulfite has also been used to convert ZVS to thiosulfate (Farroha et al 1984, Luther et al 1985, 1991, Cutter and Velinsky 1988, Ferdelman et al 1991, Henneke et al 1997) (reaction 13), followed by detection of this anion by titration with iodine (Szekeres 1974, Jørgensen et al 1979, linear sweep voltametry (Luther et al 1985, Cutter andVelinsky 1988), square wave voltametry or HPLC with fluorescence detection after derivatisation with monobromobimane (Fahey and Newton 1987) or with 2,2`dithiobis(5-nitropyridine) (Vairavamurthy and Mopper 1990).…”
Section: Review Of Methods For Zvs Determinationmentioning
confidence: 99%